(untitled) (Journal of Human Sciences, 2022)
The study aimed to identify the level of aggressive behavior of juvenile delinquents as well as to identify the differences in the level of aggressive behavior of juvenile delinquents according to the variable (type), as well as to identify the differences in the level of aggressive behavior of juvenile delinquents according to the (economic) variable and to identify the differences in the level of aggressive behavior Among juvenile delinquents according to the (educational) variable in the juvenile center in the city of Benghazi, the aggressive behavior scale was applied, which consists of (30) phrases, prepared by Arnold Bus (Bus and Mark Perry, m.perry) 1992 and translated into Arabic by Moataz Abdullah And Saleh Abu Abbah 1995, on a sample of juvenile delinquents, whose number was (100), including (30) females and (70) males, after verifying its validity and stability. Aggressive behavior was high at the level of significance (0.01). It was also found that there were statistically significant differences between males and females in the level of aggressive behavior in favor of males. It was also found that there were differences in the educational level in favor of the uneducated at the level of significance (0.01), meaning that the uneducated from The sample members were more aggressive, while we found no differences in the level of aggressive behavior according to the economic level variabl.